Stress controls heterochromatin inheritance via histone H3 ubiquitylation - Bharat Bhatt; Yi Wei; Ashis Kumar Pradhan; Jothy Dhakshnamoorthy; Martin Zofall; Hua Xiao; Drisya Vijayakumari; Shweta Jain; Hernan Diego Folco; Hongyun Qi; David A. Ball; Tatiana S. Karpova; et al. (Nature, 2026)
Abstract Heterochromatin, marked by histone H3 lysine 9 methylation, can be epigenetically inherited through cell division 1–3 , maintaining gene repression that preserves cell identity and enables adaptation to environmental challenges 2–6 . Studies on S chizosaccharomyces pombe have shown that heterochromatin propagation depends on the read–write mechanism, wherein a sufficient density of H3K9me3-modified nucleosomes, stabilized by histone deacetylases, concentrates Clr4 SUV39H on chromatin to promote further deposition of H3K9 methylation 7–9 . Whether other mechanisms control heterochromatin propagation by means of Clr4 SUV39H , a subunit of the E3 ubiquitin ligase complex ClrC 10–12 , was unknown. Here we uncover a ubiquitin-dependent heterochromatin heritability regulatory hub (HRH) that broadly governs heterochromatin propagation, even without histone deacetylase activity. The HRH is tuned by the limiting factor Raf1 DDB2 , a substrate receptor for the ClrC ubiquitin ligase. In addition to linking Clr4 SUV39H to other ClrC components on chromatin, Raf1 DDB2 acts in a dosage-dependent manner to promote ubiquitination of histone H3 at lysine 14 (H3K14ub), which is critical for heterochromatin self-propagation. HRH is intricately linked to environmentally responsive pathways, including nonsense-mediated decay (NMD) and target of rapamycin (TOR) signalling, enabling cells to adapt to changing conditions. By modulating heterochromatin propagation, cells leverage the HRH to gain resistance to antifungal agents and adapt to high temperature. Thus, heterochromatin self-propagation is actively regulated by means of H3K14ub in response to external stimuli, with broad implications for understanding mechanisms governing rapid changes in the epigenetic landscape in physiology and disease.